2011
DOI: 10.1007/s10393-011-0717-7
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, Life History, and Ecology Contribute to Differences in Amphibian Susceptibility to Ranaviruses

Abstract: Research that identifies the potential host range of generalist pathogens as well as variation in host susceptibility is critical for understanding and predicting the dynamics of infectious diseases within ecological communities. Ranaviruses have been linked to amphibian die-off events worldwide with the greatest number of reported mortality events occurring in the United States. While reports of ranavirus-associated mortality events continue to accumulate, few data exist comparing the relative susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
164
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 150 publications
(177 citation statements)
references
References 73 publications
8
164
0
5
Order By: Relevance
“…Average final survival varied minimally across the populations (0% to 4.7%) suggesting that all populations, regardless of pesticide tolerance mechanism, were highly susceptible to ranavirus. This is consistent with past work demonstrating that wood frogs are one of the most susceptible amphibian species to ranavirus infection (Hoverman etĀ al., 2011). Given the limited variability in survival across the populations, it is not surprising that we did not find a relationship with the mechanism of pesticide tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Average final survival varied minimally across the populations (0% to 4.7%) suggesting that all populations, regardless of pesticide tolerance mechanism, were highly susceptible to ranavirus. This is consistent with past work demonstrating that wood frogs are one of the most susceptible amphibian species to ranavirus infection (Hoverman etĀ al., 2011). Given the limited variability in survival across the populations, it is not surprising that we did not find a relationship with the mechanism of pesticide tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Although average TTD across the 14 populations varied more than survival (TTD ranging from 190 to 224Ā hr), we still did not find a relationship between the mechanism of pesticide tolerance and susceptibility to ranavirus. Amphibian species with intermediate levels of susceptibility to ranavirus (e.g., hylids; Hoverman etĀ al., 2011) may be better suited to address our hypotheses regarding the interaction with evolved pesticide tolerance because there is the potential for more variation in survival rates. However, wood frogs are the only amphibian species that has been examined for patterns in evolved pesticide tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, if experimental exposures show that a species dies rapidly following ranavirus exposure, then high prevalence would be most consistent with sampling during the peak of an epidemic. Several studies have reported species-level susceptibility under controlled conditions (e.g., Hoverman et al 2011;Brenes et al 2014b;Brunner et al 2015). Biological context also can be gleaned from the density of the population and the timing of the survey relative to the phenology of the organism.…”
Section: Interpreting Infection Datamentioning
confidence: 99%